Landscape change of land use in the karst region of Jinan city, North China - Qi, Shanzhong; Heng, Fuxin; Ji, Lina (Journal of Environmental Engineering and Landscape Management, 2023)
With the rapid development of urbanization, land use change has occurred in most karst mountain regions of North China over the last decade, so studying landscape pattern changes induced by urbanization would have implicational significance to regional planning and sustainability. Based on RS, GIS, and field investigation, land use change induced by urbanization in Jinan city belonging to the karst mountainous area of North China was analyzed over 30 years from 1987 to 2018, and further the landscape response of these changes was explored. The results indicate that (1) the most obvious changes have occurred in both urban/built-up land area and cropland area with rapid urbanization development in Jinan’s karst area, and the former increased by 246.4 km2 but the latter decreased by 343.3 km2 from 1987 to 2018; (2) landscape pattern of land use is profoundly changed by quick urbanization in the period from 2000 to 2018, but does not siginificently from 1987 to 2000; and (3) in the monitoring period, the cropland’s shape inclines to fragmentation and regularization, and the shapes of urban/built-up land and barren land have become increasingly distinct from the patch class level; from patch landscape level, the artificial landscape type (urban/built-up land) is increasingly dominant but the natural landscape type (grassland) is decreasingly dominant, thereby resulting in the disturbance of urban karst environment of Jinan city. Therefore, a protection policy should be taken to achieve strong urban karst sustainable development of North China.